The Effect Of Dividend, Liquidity And Asset Structure On Company Value With Total Aset Turn Over As Variables Intervening In Sector Companies Health Registered On Indonesia Stock Exchange - Elia Sundari; Sri Hermuningsih; Riskin Hidayat (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims the influence of dividends, liquidity and asset structure on company value in health sector companies listed on the Indonesia Stock Exchange during the 2019-2023 period, with Total Asset Turnover (TATO) as an intervening variable. Company value is an important indicator for investors and stakeholders, reflecting long-term performance and prospects. This research uses quantitative methods with secondary data collected through documentation and literature study, involving 11 issuers in the health sector. The research results show that dividend and liquidity policies have a positive and significant influence on company value, while asset structure also has a positive influence. TATO was not proven to mediate the influence of dividend policy, but succeeded in mediating the influence of liquidity and asset structure on firm value. This research provides important insights for investors and company managers in understanding the factors that influence company value in the Indonesian health sector.